Green innovation and renewable energy sources policies: a systematic and integrative review - Siddika, Aysa; Sarwar, Abdullah; Tareq, Mohammad Ali; Rahman, H.M. Mahfuzur; Haron, Razali (Elsevier B.V., 2025)
Research on green innovation and renewable energy sources (GIRES) has gained momentum due to severe global climate change. GIRES has become a global strategy for decentralised energy systems that employ various technologies and practices to lessen environmental impact as an alternative to traditional methods. The purpose of this study is to review the literature on GIRES policy to provide a comprehensive overview and develop insights into the state of this research field. Based on the PRISMA framework, a systematic literature review was conducted to analyse the empirical papers published in WOS and Scopus databases. A comprehensive content analysis includes a review of 64 articles to identify the key issues in GIRES policies using thematic analysis. This review explored the diversity of GIRES research on policy and evaluated it regarding publication trends, influential authors, regional focus, theoretical base, and thematic analysis. Four themes emerged from the content analysis of the 64 articles identified for inclusion: policy driver, implementation strategy, outcome, and contextual factors. The review observed that GIRES policies have significantly enhanced enterprises’ technological innovation capacities, and the successful execution of the GIRES transition depends on integrating strategies and comprehensive plans. This study addressed the importance of integrating various strategies and regulations, such as environmental policy and Green Infrastructure (GI) initiatives, to consolidate the entire renewable energy (RE) sector.